The Effect of Learning Environment, Learning Motivation, and Family Economics on Student Learning Achievement - Adhitia Hermawan, Rangga; Napisah, Napisah; Ruhiyat, Endang; Doringin, Ferry (International Journal of Economics, Management and Accounting (IJEMA), 2025)
Education is an element that cannot be separated from humans, through education humans have the responsibility of fostering humans to have good quality, intelligent, and responsible for themselves, society, nation, and country, even spiritual responsibility so that humans as learners can carry out their religious teachings properlyThis study uses cross-sectional quantitative research techniques. The population in this study was 357 students. researchers used the slovin formula in determining the number of research samples so that 191 samples were obtained in this studyThe learning environment, learning motivation and family economy have an influence on learning achievement by 37.9%The learning environment variable has no effect on learning achievement partially The learning motivation variable affects learning achievement partially The family economy variable affects learning achievement partially The learning environment, learning motivation and family economy on learning achievement simultaneously